Climate-smart agriculture - producing more with less - Pedrick, Clare (Technical Centre for Agricultural and Rural Cooperation, 2019)
In order to feed a rapidly growing population, global food production will need to increase by at least 60% by 2050. Undermining efforts to achieve that goal are shifting weather patterns, including rising temperatures, unpredictable precipitation, more severe and frequent extreme weather events and the loss of ecosystem services and biodiversity. To what extent can climate-smart agriculture offset these negative effects on prospects for food security?